Analisis Pengelolaan Parkir Tepi Jalan Umum di Kota Semarang Tahun 2012-2013 - Aditya Wisnu Priambodo; Priyatno Harsanto; Muhammad Adnan (Journal of Politic and Government Studies, 2014)
Government of Semarang City has made some efforts to improve parking management in Semarang either through self-management and partnerships. However, these efforts have not been able to in fact alleviate on street parking of the problems that had been twisted. In the last ten years, the change of system managers do not purely based on the vision of improved parking management in Semarang, but is more likely to be influenced by the interests of its officials. Nepotism found in the implementation of the on street parking management policies common in Semarang. Partnership policies made by the government deliberately decided and reserved for its officials partners. Mayor of Semarang became the most influential figure in the election Dishubkominfo partners in managing on street parking, because the partnership policy is done in every turn of the Mayor of Semarang. Semarang City Government should start thinking about alternative policies to achieve a good parking management. Building a parking deck and parking system could be an option to subscribe for Semarang City Government, and the partnership is the best option when resource limitations constrain the government to make it happen. Keywords: Management, On Street Parking, and Partnership